Unilateral Mastication Evaluated Using Asymmetric Functional Tooth Units as a Risk Indicator for Hearing Loss - Joo-Young Lee; Eun-Song Lee; Gyung-Min Kim; Hoi-In Jung; Jeong-Woo Lee; Ho-Keun Kwon; Baek-Il Kim (Journal of Epidemiology, 2019)
Background: Some previous studies reported hearing ability can be reduced by impaired masticatory ability, but there has been little evidence reported of an association between hearing loss and unilateral mastication. Therefore, this study aimed to investigate the relationship between unilateral mastication (UM), estimated from individual functional tooth units (FTUs), and hearing loss in a representative sample of Korean adults. Methods: The analyzed data were obtained from 1,773 adults aged 40–89 years who participated in Korean national survey. Hearing loss was defined as a pure-tone average of >25 dB at frequencies of 0.5, 1, 2, and 4 kHz in either ear. In each subject, UM was calculated as the difference in the sums of the FTU scores, which is an index of posterior tooth occlusion, on the two sides of the oral cavity. The scores were used to classify the UM into low, moderate, and high. The adjusted odds ratios (aORs) and their 95% confidence intervals (CIs) were calculated in multivariable logistic regression analyses. Results: When controlling for sociodemographic factors, the aOR for hearing loss was 3.12 (95% CI, 1.21–8.03) for high UM relative to low UM. This association remained in a fully-adjusted model containing factors related to noise exposure (aOR 2.88; 95% CI, 1.12–7.46). Conclusion: Adults with high UM as measured using FTUs showed a higher occurrence of hearing loss than those with low UM.